Peran Literasi Digital terhadap Kemampuan Membaca Kritis dalam Pembelajaran Bahasa Indonesia (Kajian Literature Review) - Weti Yunaika (Hikamatzu | Journal of Multidisciplinary, 2025)
This literature review aims to examine the role of digital literacy in enhancing critical reading skills in Indonesian language learning. The findings reveal that digital literacy significantly contributes to students' ability to access, evaluate, and process information critically. Through the use of digital platforms and resources, learners are encouraged to engage in reflective and analytical thinking, which is essential for developing critical reading competencies. Furthermore, digital literacy facilitates broader access to diverse texts and interactive learning environments, promoting deeper comprehension and interpretation. Therefore, integrating digital literacy into Indonesian language education is essential to cultivate critical, adaptive, and information-literate readers in the digital era